Maternal peripheral blood platelet‐to‐white blood cell ratio and platelet count as potential diagnostic markers of histological chorioamnionitis‐related spontaneous preterm birth. Issue 4 (4th February 2019) - Qiu, Liyin; Pan, Mian; Zhang, Ronglian; Ren, Kunhai
Abstract : Background: Histological chorioamnionitis (HCA) is one of the leading causes of spontaneous preterm birth, thus, to identify novel biomarkers for the early diagnosis of HCA is in a great need. Objective: To investigate the diagnostic value of maternal peripheral blood platelet‐to‐white blood cell ratio (PLT/WBC) and platelet (PLT) counts in HCA‐related preterm birth. Methods: A total of 400 patients with preterm birth were enrolled in this study: non‐HCA group (n = 193) and HCA group (n = 207), and 87 full‐term pregnancies were enrolled as the control. The peripheral blood of the participators was collected, and the neutrophil count, WBC count, platelet count, and levels of C‐reactive protein (CRP) and procalcitonin were recorded, and the platelet‐to‐white blood cell ratio (PLT/WBC) of the participators was calculated. Receiver operating characteristic (ROC) curve has been drawn to show the sensitivity and specificity of PLT/WBC and PLT count for the diagnosis of HCA‐related spontaneous preterm birth patients. Results: The neutrophil count, WBC count, and procalcitonin show no significant differences among the three groups, and the PLT count, PLT/WBC, and CRP ( P  < 0.05) were significantly increased in HCA group compared with non‐HCA group; moreover, the area under the curve (AUC) of PLT/WBC, PLT, and CRP was 0.744 (95% confidence interval [CI], 0.6966‐0.7922), 0.8095 (95% CI, 0.7676‐0.8514), and 0.5730 (95% CI, 0.5173‐0.6287), respectively. Conclusion: Platelet count and PLT/WBC may become a potential biomarker of HCA‐related spontaneous preterm birth.